Mongolian animal protein’s resource and usage problem - Chimegee, N; Damdinsuren, L; Lkhagvasuren, S; Badamkhand, L (Mongolian Journal of Agricultural Sciences, 2014)
In a year, it’s calculated that to prepare 11885 ton animal internal organ’s and derivative raw materials protein for food stuff and defined ways of usage DOI: http://dx.doi.org/10.5564/mjas.v11i2.216 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.49-53